Focused Issues and Trends in Economic Research from Germany - Joachim Wagner (MDPI, 2023)
In recent years we all faced a large number of new and challenging economic problems (including the financial crisis, the COVID pandemic, energy shortage due to the war in the Ukraine, and a comeback of inflation). Economists contribute to the analysis of these and many other problems by using elaborate econometric methods and newly available data, often collected at the micro level of the economic agents (firms and households). This special issue of Economies collected applied economic papers with a focus on Germany, one of the leading economies in Europe. Both original research articles and reviews are welcomed. Research areas may include (but are in no way limited to) the following: labour market, industrial relations, migration, health, innovation, digitalization, international firm activities, firm behaviour and performance.
Keywords: 330